TagPAINT: covalent labelling of genetically encoded protein tags for DNA-PAINT imaging. Issue 12 (11th December 2019) - Nieves, Daniel J.; Hilzenrat, Geva; Tran, Jason; Yang, Zhengmin; MacRae, Hugh H.; Baker, Matthew A. B.; Gooding, J. Justin; Gaus, Katharina
Abstract : Recently, DNA-PAINT single-molecule localization microscopy (SMLM) has shown great promise for quantitative imaging; however, labelling strategies thus far have relied on multivalent and affinity-based approaches. Here, the covalent labelling of expressed protein tags (SNAP tag and Halo tag) with single DNA-docking strands and application of SMLM via DNA-PAINT is demonstrated. tagPAINT is then used for T-cell receptor signalling proteins at the immune synapse as a proof of principle.